2020
DOI: 10.1177/1538574420968670
|View full text |Cite
|
Sign up to set email alerts
|

Distal Retrograde Access for Infrainguinal Arterial Chronic Total Occlusions: A Prospective, Single Center, Observational Study in the Office-Based Laboratory Setting

Abstract: Objective: To assess the safety and efficacy of retrograde arterial recanalization of infrainguinal CTOs in the OBL setting. Methods: Consecutive patients who underwent interventions for lower extremity CTOs in the OBL setting by a single vascular surgeon were evaluated (January 2013-November 2017). If antegrade crossing was not possible, then a retrograde distal approach was used. Patient characteristics, CTO location, procedural time, contrast, anticoagulation and radiation doses and costs were recorded. Pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 12 publications
5
14
0
Order By: Relevance
“…Previous investigations have observed a similar low complication rate associated with distal vascular access sites. [11][12][13][14]33,34,36,45 The rate of VASCs was also comparable to other | 1115 published studies in the endovascular field related to both femoral and radial access. [46][47][48][49][50] Patel et al 51 compared the transradial and tibio-pedal approach in femoro-popliteal CTOs, highlighting higher major adverse events at 30 days in the transradial access arm (5% vs. 0%).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Previous investigations have observed a similar low complication rate associated with distal vascular access sites. [11][12][13][14]33,34,36,45 The rate of VASCs was also comparable to other | 1115 published studies in the endovascular field related to both femoral and radial access. [46][47][48][49][50] Patel et al 51 compared the transradial and tibio-pedal approach in femoro-popliteal CTOs, highlighting higher major adverse events at 30 days in the transradial access arm (5% vs. 0%).…”
Section: Discussionsupporting
confidence: 86%
“…Htun et al 13 observed a shorter fluoroscopy time, as expected, when retrograde tibio‐pedal access is performed as the primary approach. The dose‐area product and the cumulative air kerma don't differ from that of other investigations in this field in which different distal access sites were used 12,14 . Retrograde crossing of femoro‐popliteal occlusions with tibial access is associated with similar procedure duration, fluoroscopy time and radiation exposure, compared to other distal vascular access sites.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations